Cost-effectiveness of a preferred intensity exercise programme for young people with depression compared with treatment as usual: an economic evaluation alongside a clinical trial in the UK. Issue 11 (26th November 2017) - Turner, David; Carter, Tim; Sach, Tracey; Guo, Boliang; Callaghan, Patrick
Abstract : Objectives: To assess the cost-effectiveness of preferred intensity exercise programme for young people with depression compared with a treatment as usual control group. Design: A 'within trial' cost-effectiveness and cost-utility analysis conducted alongside a randomised controlled trial. The perspective of the analysis was the UK National Health Service and social services. Setting: The intervention was provided in a community leisure centre setting. Participants: 86 young people aged 14–17 years attending Tier 2 and Tier 3 CAMHS (Child and Adolescent Mental Health Services) outpatient services presenting with depression. Interventions: The intervention comprised 12 separate sessions of circuit training over a 6-week period. Sessions were supervised by a qualified exercise therapist. Participants also received treatment as usual. The comparator group received treatment as usual. Results: We found improvements in the Children's Depression Inventory-2 (CDI-2) and estimated cost-effectiveness at £61 per point improvement in CDI-2 for the exercise group compared with control. We found no evidence that the exercise intervention led to differences in quality-adjusted life years (QALY). QALYs were estimated using the EQ-5D-5L (5-level version of EuroQol-5 dimension). Conclusions: There is evidence that exercise can be an effective intervention for adolescents with depression and the current study shows that preferred intensity exercise could also represent a cost-effective intervention in terms of the CDI-2. Trial registration number: NCT01474837.